Linguistic Creativity of the Indonesian for Foreign Speakers (BIPA) Students at the Morphological, Syntactic, and Semantic Levels - Rahmi Yulia Ningsih; Zainal Rafli; Endry Boeriswati (Lingua Cultura, 2021)
The research aimed to describe the forms of linguistic creativity of BIPA students at the morphological, syntactic, and semantic levels. The research method used was descriptive qualitative with content analysis techniques. The research data were 78 sentences written by BIPA students at Bina Nusantara University academic year 2020/2021. The results show that BIPA students’ sentences have linguistic creativity in the form of the morphological, syntactic, and semantic levels sentences. At the morphological level, the process of linguistic creativity in words is carried out by (1) inserting foreign terms into sentences, (2) using non-standard words, and (3) abbreviating words. While in phrases, linguistic creativity is done by (1) reversing the structure of the phrase, (2) forming nominal phrases with less common word pairs, and (3) forming nominal phrases by incorporating elements of student culture. At the syntactic level, linguistic creativity is carried out in the form of compiling compound sentences with the expansion of descriptions, expansion of objects, expansion of subjects, and expansion of predicates. At the semantic level, linguistic creativity is manifested in the form of the figure of speech: personification, simile, hyperbole, repetition, and metaphor.